Social Function Levels of Families that Live with Elderly - Linda Kurniawati; Rina Anggraeni; Riani Pradara Jati (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
10,34% of the population of Central Java Province are the elderly people. The increasing number of the elderly people results in the indirect negative impact on the famies values which influence the drop of the elderly people’s welfare, lack of their role and status in the families, and loss of supports from their families. This research aims to explore the levels of the social functions of their families in which the elderly people live in Kedungsuren Village seen from the points of views of adaptation, partnership, growth, affection, and resolve. This research was conducted with the domain of quantitative design with a descriptive survey method. The total sampling technique was applied to 82 respondents. The instrument in the data collection was an APGAR family questionnaire. This research used a univariate analysis. The results of the research show that 61 respondents(74,4%), with whom the elderly people live, had less-healthy living conditions while 49 respondents (59,8%) were sometimes satisfied with social function adaptation. Similarly, 44 respondents (53,7%) were sometimes satisfied with the partnership of social functions and 35 respondents (42,7%) were always satisfied with the growth of social functions. 50 respondents (61,0%) were always satisfied with the affection of social functions. In addition, 72 respondents (87,8%) were always satisfied with the resolve of social functions. The families are expected to be able to improve communication, supports, and attention given to the elderly people in order to improve the families’ and the elderly people’s social functions. The level of social function of families living with the elderly in Kedungsuren Village is dominated by the level of unhealthy social function.